Autophagy Induced by Ischemic Preconditioning is Essential for Cardioprotection - Huang, Chengqun (Springer US, 2010)
Based on growing evidence linking autophagy to preconditioning, we tested the hypothesis that autophagy is necessary for cardioprotection conferred by ischemic preconditioning (IPC). We induced IPC with three cycles of 5 min regional ischemia alternating with 5 min reperfusion and assessed the induction of autophagy in mCherry-LC3 transgenic mice by imaging of fluorescent autophagosomes in cryosections. We found a rapid and significant increase in the number of autophagosomes in the risk zone of the preconditioned hearts. In Langendorff-perfused hearts subjected to an IPC protocol of 3 × 5 min ischemia, we also observed an increase in autophagy within 10 min, as assessed by Western blotting for p62 and cadaverine dye binding. To establish the role of autophagy in IPC cardioprotection, we inhibited autophagy with Tat-ATG5(K130R), a dominant negative mutation of the autophagy protein Atg5. Cardioprotection by IPC was reduced in rat hearts perfused with recombinant Tat-ATG5(K130R). To extend the potential significance of autophagy in cardioprotection, we also assessed three structurally unrelated cardioprotective agents—UTP, diazoxide, and ranolazine—for their ability to induce autophagy in HL-1 cells. We found that all three agents induced autophagy; inhibition of autophagy abolished their protective effect. Taken together, these findings establish autophagy as an end-effector in ischemic and pharmacologic preconditioning.